Media industry studies - Herbert, Daniel; Lotz, Amanda D.; Punathambekar, Aswin (2020)
"This text provides the roadmap to the vibrant area of Media Industry studies"--
The origins of media industry studies -- Individuals and roles -- "Production" cultures -- Organizations -- Industries and practices -- The macro view -- Conclusion : future directions for media industry studies.
Keywords: Mass media -- Study and teaching